Identification and Validation of Biglycan as Prognosis and Therapy Markers for Patients with Stomach Adenocarcinoma - Shao, Changming (Int J Gen Med, 2021)
OBJECTIVE: Previous studies have confirmed the biglycan (BGN) as a core gene in stomach adenocarcinoma (STAD). Present study aimed at conducting further investigations to reveal the potential function of BGN in STAD. METHODS: The mRNA and protein expressions of BGN in STAD were firstly evaluated, followed by immune infiltration analyses. The influence of BGN expression on the overall survival of STAD patients was subsequently analyzed, and a restrict survival analysis was performed as well. The protein–protein interaction (PPI) network analysis on the co-expressed genes with BGN was finally adopted to obtain the most important module in the whole network, and significant Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway associated with hub genes within the main module was further predicted. RESULTS: (1) We verified the mRNA high expression of BGN in STAD (all P<0.05), and higher expression was observed in patients with stage 4 (P<0.001) and grade 3 (P<0.001). The BGN protein was mainly localized to the golgi apparatus, and protein expression displayed an individual difference. (2) Immune infiltration analysis showed the strongest correlation between BGN expression and abundance of natural killer cell (P<0.001), Transforming Growth Factor beta 1 (TGFB1) (P<0.001), TNF Receptor Superfamily Member 4 (TNFRSF4) (P<0.001) and C-X-C Motif Chemokine Ligand 12 (CXCL12) (P<0.001) in STAD. BGN expression was also correlated to immune subtypes (P=0.0347) and molecular subtypes (P=0.0263) in STAD. (3) High expression of BGN shortened the overall survival time of STAD patients (all P<0.01). The influence of BGN expression on the prognosis was statistically affected by several clinical phenotypes and cohorts of patients. Cox regression showed that BGN can be considered as a prognostic predictor of STAD (P<0.05). (4) Pathway analysis indicated that BGN possibly participated in ECM–receptor interaction, focal adhesion, human papillomavirus infection and PI3K-Akt signaling pathway (all P<0.001). CONCLUSION: BGN was highly expressed in STAD, implying a poor prognosis of patients. Relevant signal pathways associated with BGN were distinguished as well. BGN could be used as a potential therapeutic biomarker for STAD.